Estrategias de posicionamiento en la boutique exclusividades de la ciudad de Babahoyo. - Gonzalez Gonzalez, Damaris Lizeth (2022)
This case study aims to analyze whether the Boutique Exclusivities company has used strategies to be able to position itself in the Babahoyo canton market. For this reason, it is intended to answer research questions such as Does Boutique Exclusivities use positioning strategies to achieve consolidation in the market? Is there any evaluation that determines the effect of the applied positioning strategies?; for which the quantitative methodology will be used, which will preferably allow the use of quantifiable information to describe or try to explain the phenomena that will be analyzed in this investigation. A descriptive type of research was used that allows providing objective, precise and systematic characteristics of the phenomena without trying to infer causal relationships, to this is added the application of the documentary method when using the available bibliography to support the research; The inductive method was also used, which allowed obtaining general conclusions from particular premises. The survey technique applied to people in general was used to know the effectiveness of the company's strategies, for which a structured questionnaire was applied to 62 people between clients and non-clients in order to obtain the necessary information from the case study. The research line in which this research is based is "Financial, administrative, tax, audit and control management" and the subline that belongs to the Commercial Engineering career called "Marketing and commercialization".